2013
DOI: 10.1523/jneurosci.1114-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Nonvisual and Visual Object Shape Representations in Occipitotemporal Cortex: Evidence from Congenitally Blind and Sighted Adults

Abstract: Knowledge of object shape is primarily acquired through the visual modality but can also be acquired through other sensory modalities. In the present study, we investigated the representation of object shape in humans without visual experience. Congenitally blind and sighted participants rated the shape similarity of pairs of 33 familiar objects, referred to by their names. The resulting shape similarity matrices were highly similar for the two groups, indicating that knowledge of the objects' shapes was large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 30 publications
9
51
0
Order By: Relevance
“…The resulting representational similarity analysis quantifies the similarity of voxel patterns across modalities, comparing every object to every other object as well as to itself. Previous studies have calculated neural similarity matrices separately for each modality and then subsequently correlated those matrices (e.g., Peelen et al, 2014). Such an approach amounts to showing that neural correlations among objects in one modality correlate with the neural correlations among objects in another modality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The resulting representational similarity analysis quantifies the similarity of voxel patterns across modalities, comparing every object to every other object as well as to itself. Previous studies have calculated neural similarity matrices separately for each modality and then subsequently correlated those matrices (e.g., Peelen et al, 2014). Such an approach amounts to showing that neural correlations among objects in one modality correlate with the neural correlations among objects in another modality.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research shows that LOC represents visual information about object shape (Grill-Spector, Kourtzi, & Kanwisher, 2001; Kourtzi & Kanwisher, 2001) and responds to haptic exploration of objects in sighted and congenitally blind individuals (Naumer et al, 2010; Amedi, Jacobson, Hendler, Malach, & Zohary, 2002; James et al, 2002; Amedi, Malach, Hendler, Peled, & Zohary, 2001). Furthermore, neural shape similarity matrices from blind participants are correlated with neural shape similarity matrices from sighted individuals (Peelen, He, Han, Caramazza, & Bi, 2014), suggesting that LOC is biased to represent object shape even if the principal modality of input is not vision.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inferior temporal gyrus is part of the ventral visual stream and subserves shape perception and recognition memory for patterns, faces and objects (43,44). In a previous study, participants reporting greater depersonalization/derealization showed reduced theta activity in the temporal lobe (45).…”
Section: Smaller Grey Matter Volume Associated With Dissociation (Depmentioning
confidence: 90%